PENGELOLAAN TRIPLE CONSTRAINTS DALAM PEMBANGUNAN MASJID WAKAF - Septiono Eko Bawono (Jurnal Taman Vokasi, 2015)
Islamic Relief Organization Saudi Arabia channeled 21 units waqf mosque in 2015. They distributed into five districts in Yogyakarta. The development focused on managing triple constraints in order to complete the job within four months and to control risk factors. The method used to measure the success rate of this program is calculating the deviation value between realization progress and plan progress with the S Curve. This study aims to identify the successful implementation of triple constraints management which is able to make a major contribution to the risk management effectively and efficiently. The success of this project looks at the accumulated deviation of each month: M1 = -7.75%, -19.01% M2 = M3 = 18:07%, and M4 = 8.69%.